2004
DOI: 10.1038/sj.gt.3302159
|View full text |Cite
|
Sign up to set email alerts
|

Dextran–spermine polycation: an efficient nonviral vector for in vitro and in vivo gene transfection

Abstract: Dextran-spermine cationic polysaccharide was prepared by means of reductive amination between oxidized dextran and the natural oligoamine spermine. The formed Schiff-base imine-based conjugate was reduced with borohydride to obtain the stable amine-based conjugate. The transfection efficiency of the synthetic dextran-spermine was assessed in vitro on HEK293 and NIH3T3 cell lines and found to be as high as the DOTAP/Chol 1/1 lipid-based transfection reagent. Modification of the dextran-spermine polycation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(118 citation statements)
references
References 47 publications
1
110
1
Order By: Relevance
“…17 Incorporation of plasmid DNA into dextran-spermine was performed by simply mixing two materials at various charge ratios (N/P, indicated as the molar ratio of the spermine nitrogen of dextran-spermine to the phosphate molecules of plasmid DNA) in aqueous solution. Briefly, 150 µL of 0.1 M phosphate-buffered saline solution (PBS, pH 7.4) containing 2.5, 5, 10, 25, and 100 µg of dextran-spermine was added to the same volume of PBS containing 10 µg of plasmid DNA.…”
Section: Fabrication and Characterization Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Incorporation of plasmid DNA into dextran-spermine was performed by simply mixing two materials at various charge ratios (N/P, indicated as the molar ratio of the spermine nitrogen of dextran-spermine to the phosphate molecules of plasmid DNA) in aqueous solution. Briefly, 150 µL of 0.1 M phosphate-buffered saline solution (PBS, pH 7.4) containing 2.5, 5, 10, 25, and 100 µg of dextran-spermine was added to the same volume of PBS containing 10 µg of plasmid DNA.…”
Section: Fabrication and Characterization Of Nanoparticlesmentioning
confidence: 99%
“…We have reported that the dextran-spermine based polycations have been found to be highly effective as nonviral vectors in transfecting many different cells in vitro. [11][12][13][14][15][16][17] Our recent study also demonstrated that electrospun poly (glycolic acid) (PGA)/ collagen nanofibers significantly enhanced cell adhesion compared with PGA/collagen microfibers. 18 Based on these results, the present study aims to fabricate a tissue-like 3D transgene cell construct for use as a therapeutic cell-based gene delivery system or as an in vitro model system for testing genetic manipulations to understand the effects of gene expression on tissue development.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41] Our previous study demonstrated that dextran significantly enhanced in vitro and in vivo gene trasnfection. 42 To give the dextran a cationized charge, which is necessary for the formation of polyion complexes with plasmid DNA, spermine was introduced to the hydroxyl groups of dextran. The cationized dextran was then reacted with poly(ethylene glycol) (PEG) and mixed with NK4 plasmid DNA in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of PEG in gene vectors in various creative capacities is a widely used strategy for improving the polyplex solubility and reduce polyplex aggregation and prolong the circulation time [2,5,7,12,28,48]. Both spermine and aspartic acid, being natural materials are biodegradable and its copolymer with an aliphatic amide bonding is expected to be also biodegradable [50].…”
Section: Resultsmentioning
confidence: 99%